Putusan Bebas dalam Tindak Pidana Pencabulan - Lestari, Ella Wahyu; Iriyanto, Echwan; AN, Dodik Prihatin (University of Jember, 2016)
Obscene crime is the immoral act that has attack the physical and psychic of the victims continuously, especially if the victims are minors, so it is required to be appropriate law enforcement. Obscene against children is a case that has difficult proofs, so it is can not be judged only by manifestations without based on the beliefs of judges and related theories. This article contains 2 (two) issues, namely: (1) Is the singular indictment formulated by the public prosecutor in verdict number: 52/Pid.B/2014/PN.Lok under the defendant's conduct? (2) Is the judge's consideration who was declared that the defendant is not guilty doing the obscene crime in verdict number: 52/Pid.B/2014/PN.Lwk under the facts revealed in the court.This paper uses a normative juridical research, by statute approach (statute approach) and conceptual approach (conceptual approach). Obtained conclusions that (1) the singular indictment formulated by the public prosecutor in verdict number: 52/Pid.B/2014/PN.Lwk is under the defendant's conduct (2) the judge consideration who was declared that the defendant is not guilty doing the obscene crime in verdict number: 52/Pid.B/2014/PN.Lwk is not following the facts revealed in the court. KEYWORDS: Obscene, Acquital, Indictmen, Judge Consideration.